Regulation of sodium absorption by canine tracheal epithelium. - Cullen, J J (1987)
To regulate the quantity of respiratory tract fluid, the airway epithelium either secretes chloride, Cl-, or reabsorbs sodium, Na+. Many secretagogues inhibit Na+ absorption, but the decrease may result from a fall in the electrochemical gradient for Na+ absorption. We examined regulation of Na+ absorption independent of Cl- secretion, by bathing canine tracheal epithelium in Cl--free, gluconate Ringers solution. Prostaglandin E2, 2-chloroadenosine, and isoproterenol increased short-circuit current (Isc) and the rate of Na+ absorption. In contrast, indomethacin, which inhibits endogenous prostaglandin production, decreased Isc. These agents regulate cellular levels of cAMP; direct addition of 8-Br-cAMP also acutely increased Isc. We examined chronic regulation of Na+ absorption in cell monolayers grown on permeable supports in serum-free media. Exposure to aldosterone for two days increased baseline Isc by 50% and the amiloride-inhibitable current by 55%. These data indicate that Na+ absorption is both acutely and chronically regulated in the airway epithelium.